2016
DOI: 10.3390/catal6120184
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of (+)-Nootkatone via Dark Singlet Oxygenation of Valencene: The Triple Role of the Amphiphilic Molybdate Catalyst

Abstract: Efficient one-pot catalytic synthesis of (+)-nootkatone was performed from (+)-valencene using only hydrogen peroxide and amphiphilic molybdate ions. The process required no solvent and proceeded in three cascade reactions: (i) singlet oxygenation of valencene according to the ene reaction; (ii) Schenck rearrangement of one hydroperoxide into the secondary β-hydroperoxide; and (iii) dehydration of the hydroperoxide into the desired (+)-nootkatone. The solvent effect on the hydroperoxide rearrangement is herein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Several chemical synthetic strategies have been developed via the Robison annulation, intramolecular Sakurai reaction, and Diels-Alder/Aldol tandem reaction, etc. 7 However, the mentioned above generally provide racemic (AE)-nootkatone. One-pot synthesis of (+)-nootkatone through singlet oxygenation of (+)-valencene has been realized with carcinogenic tert-butyl hydroperoxide in combination with Co(OAc) 2 , Cu(OAc) 2 or V(OAc) 2 catalysts.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several chemical synthetic strategies have been developed via the Robison annulation, intramolecular Sakurai reaction, and Diels-Alder/Aldol tandem reaction, etc. 7 However, the mentioned above generally provide racemic (AE)-nootkatone. One-pot synthesis of (+)-nootkatone through singlet oxygenation of (+)-valencene has been realized with carcinogenic tert-butyl hydroperoxide in combination with Co(OAc) 2 , Cu(OAc) 2 or V(OAc) 2 catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…One-pot synthesis of (+)-nootkatone through singlet oxygenation of (+)-valencene has been realized with carcinogenic tert-butyl hydroperoxide in combination with Co(OAc) 2 , Cu(OAc) 2 or V(OAc) 2 catalysts. 7 The explosive, corrosive, and toxic heavy metal chemocatalyst requirements of the chemical approaches call for greener and more effective methods for (+)-valencene and (+)-nootkatone preparation. Previously, (+)-valencene extracted from Valencia orange was converted into (+)-nootkatone by biotransformation using Aspergillus, Rhodococcus, Chlorella, Mucor species Botryodiplodia theobromae 1368, Yarrowia lipolytica 2.2ab, and Phanerochaete chrysosporium.…”
Section: Introductionmentioning
confidence: 99%
“…It offers a nice alternative to the “dehydration” of allylic hydroperoxides through acetylation and elimination, , but requires however a mixture of iodosobenzene diacetate and magnesium monoperoxyphthalate as oxidant. Alternatively, we have also recently reported a new pathway for the dehydration of valencene hydroperoxides using molybdate anion as a catalyst without any additives, leading to the corresponding enone, that is, the flavor nootkatone …”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, we have also recently reported a new pathway for the dehydration of valencene hydroperoxides using molybdate anion as a catalyst without any additives, leading to the corresponding enone, that is, the flavor nootkatone. 18 Molybdate anion readily forms peroxo complexes in the presence of hydrogen peroxide. 19 Many of them can catalyze various oxidative reactions.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Some unsafe oxidizing agents such as tert -butyl peracetate (Wilson & Shaw, 1978 ) or tert -butyl hydroperoxide was used to catalyze (+)-valencene to synthesize (+)-nootkatone (Salvador & Clark, 2002 ). Hong et al found that hydrogen peroxide and amphiphilic molybdate ions could be used to catalyze (+)-valencene to synthetize (+)-nootkatone (Hong et al, 2016 ). It was also found that (+)-valencene could be oxidated by metalloporphyrins to produce (+)-nootkatone for the first time (de Melo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%